THE UNTRANSLATABILITY OF TRANSLATION IN ALIAH SCHLEIFER’S MARY THE BLESSED VIRGIN OF ISLAM INTO AGUNG PRIHANTORO’S MARYAM SANG PERAWAN SUCI - Sarlan Sarlan (University of Muhammadiyah Purwokerto, 2009)
The paper is to identify the factors of unstranslatability, to describe the strategies applied by translator in handling the problem, and to find out the effect of unstranslatability to the readibility of the text, and the readibilit level of the text. The anaysis shows that there are two factors of untranslatability: linguistics and culture. Cultural factor is more dominant because the original text deals with the Arabic culture and the religion issue, islamic religion. In solving the untranslatability problem, translator applied a contrastive analysis by : (1) italizing the untranslatable concepts; (2) replacing it by the similar concept in the target language (including the spelling modification); and (3) describing the concept by putting annotation, clarifying phrase and other things to clarify. Based on the questionnaire, the translated text is proved to have a high readibility level. However, there is a tendency that the book is more appropriate for the readers who are used to the religious terms, and not so for the common readers.